Acceleration Strategies Based on an Improved Bubble Packing Method (Communications in Computational Physics, 2014)
The bubble packing method can generate high-quality node sets in simpleand complex domains. However, its efficiency remains to be improved. This study isa part of an ongoing effort to introduce several acceleration schemes to reduce the costof simulation. Firstly, allow the viscosity coefficient c in the bubble governing equations to change according to the coordinates of the bubbles which are defined separatelyas odd and normal bubbles, and meanwhile with the saw-shape relationship with timeor iterations. Then, in order to relieve the over crowded initial bubble placement, twocoefficients $ω_1$ and $ω_2$ are introduced to modify the insertion criterion. The range ofthose two coefficients are discussed to be $ω_1$=1, $ω_2$∈[0.5,0.8]. Finally, a self-adaptivetermination condition is logically set when the stable system equilibrium is achieved.Numerical examples illustrate that the computing cost can significantly decrease byroughly 80% via adopting various combination of proper schemes (except the uniformplacement example), and the average qualities of corresponding Delaunay triangulation substantially exceed 0.9. It shows that those strategies are efficient and can generate a node set with high quality.